ENERGY CONSUMPTION AND NIGERIAN ECONOMIC GROWTH: AN EMPIRICAL ANALYSIS - Onakoya, Adegbemi Babatunde; Onakoya, Adegbemi Olatunde; Jimi - Salami, Olalekan Adejuwon; Odedairo, Babatunde Omoniyi (European Scientific Journal, ESJ, 2013)
ï»¿The study evaluates thecausal nexus between energy consumption andNigeria's economic growth for the period of 1975 to 2010. Secondary time-series data were analyzed using co-integration and ordinary least square techniques. Co-integration results show a long run relationship among the variables. The result shows that in the long run, total energy consumption had a similar movement with economic growth except for coal consumption. The empirical results reveal that petroleum, electricity and the aggregate energy consumptionhave significant and positive relationship with economic growth in Nigeria. However, gas consumption although positive, does not significantlyaffecteconomic growth. The impact of coal was negative but significant; therefore this is just the time to increase the use this resource to the nation's benefit. Therefore, the study recommends that government should encourage a level- playing field for all energy forms available in the country by diversifying its power-generation portfolio. Also, the government should continue to collaborate with the private sector within the context of public-private- partnership (PPP) to further exploit the opportunities in the sector in order to increase economic growth.